S,S‐Chiral Linker Induced U Shape with a Syn‐facial Sensitizer and Photocleavable Ethene Group - Ghosh, Goutam (2019)
There is a major need for light-activated materials for the release of sensitizers and drugs. Considering the success of chiral columns for the separation of enantiomer drugs, we synthesized an S,S-chiral linker system covalently attached to silica with a sensitizer ethene near the silica surface. First, the silica surface was modified to be aromatic rich, by replacing 70% of the surface groups with (3-phenoxypropyl)silane. We then synthesized a 3-component conjugate [chlorin sensitizer, S,S-chiral cyclohexane and ethene building blocks] in 5 steps with a 13% yield, and covalently bound the conjugate to the (3-phenoxypropyl)silane-coated silica surface. We hypothesized that the chiral linker would increase exposure of the ethene site for enhanced 1 O2-based sensitizer release. However, the chiral linker caused the sensitizer conjugate to adopt a U shape due to favored 1,2-diaxial substituent orientation; resulting in a reduced efficiency of surface loading. Further accentuating the U shape was p–p stacking between the (3-phenoxypropyl)silane and sensitizer. Semiempirical calculations and singlet oxygen luminescence data provided deeper insight into the sensitizer’s orientation and release. This study has lead to insight on modifications of surfaces for drug photorelease and can help lead to the development of miniaturized photodynamic devices.